2020
DOI: 10.1016/j.celrep.2020.108238
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota-Induced Changes in β-Hydroxybutyrate Metabolism Are Linked to Altered Sociability and Depression in Alcohol Use Disorder

Abstract: Highlights d Gut alterations are related to impaired sociability in alcohol use disorder patients d Human-to-mice microbiota transplantation reproduces metabolic and behavioral disorders d Microbial ethanol production is linked to reduced b-hydroxybutyrate (BHB) synthesis d In mice and humans, BHB level is associated with depression and social impairments

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
113
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(117 citation statements)
references
References 97 publications
2
113
0
2
Order By: Relevance
“…However, these associations do not persist when taking into account potential confounding factors like sociodemographic characteristics, BMI, energy intake and tobacco use. The observation of a relationship between lipid metabolism dysregulation and the importance of symptoms of AUD as well as changes in myelin synthesis has recently been highlighted by a translational study from our research group [62]. Together, these data stress the importance of lipid intake and metabolism in the development of AUD.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, these associations do not persist when taking into account potential confounding factors like sociodemographic characteristics, BMI, energy intake and tobacco use. The observation of a relationship between lipid metabolism dysregulation and the importance of symptoms of AUD as well as changes in myelin synthesis has recently been highlighted by a translational study from our research group [62]. Together, these data stress the importance of lipid intake and metabolism in the development of AUD.…”
Section: Discussionmentioning
confidence: 86%
“…We have already shown that the gut microbiota of alcoholic patients is altered [2]. It has been shown in animal studies that gut microbiota could influence anxiety and social behaviour [62,70,71]. In humans, microbial changes caused by fermented foods induce changes in mood [20,72].…”
Section: Discussionmentioning
confidence: 98%
“…For instance, we have described two different behavioral profiles in mice that had intermittent or continuous access to HFD during adolescence [ 56 ]. In addition, a recent study has described a unique gut microbial profile in BED patients compared to obese individuals [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Leclercq and collaborators demonstrated that alterations in gut permeability and microbiome composition (principally decreases in genera from Ruminococcaceae family) were associated with craving, a hallmark of addiction (Leclercq et al, 2012(Leclercq et al, , 2014. More recently these authors have shown that gut microbiota induce changes in metabolism linked to alterations in sociability and depression in AUD (Leclercq et al, 2020). Recently, we have proposed a framework of how emotional dysregulation and alcohol-related microbiome dysbiosis could contribute to accelerate the addiction cycle in AUD (Carbia et al, 2020), highlighting the importance of integrating disparate aspects such as microbiota for advancing in the understanding of addiction.…”
Section: Implication For Substance Use Disordersmentioning
confidence: 99%